Antifibrinolytics Reduce Blood Loss in Adult Spinal Deformity Surgery. Issue 8 (15th April 2015) - Peters, Austin; Verma, Kushagra; Slobodyanyuk, Kseniya; Cheriyan, Thomas; Hoelscher, Christian; Schwab, Frank; Lonner, Baron; Huncke, Tessa; Lafage, Virginie; Errico, Thomas
<x xml:space="preserve">Abstract</x> Study Design. This is a prospective, randomized, double-blinded comparison of tranexamic acid (TXA), epsilon aminocaproic acid (EACA), and placebo used intraoperatively in patients with adult spinal deformity. Objective. The purpose of this study was to provide high-quality evidence regarding the comparative efficacies of TXA, EACA, and placebo in reducing blood loss and transfusion requirements in patients undergoing posterior spinal fusion surgery. Summary of Background Data. Spine deformity surgery usually involves substantial blood loss. The antifibrinolytics TXA and EACA have been shown to improve hemostasis in large blood loss surgical procedures. Methods. Fifty-one patients undergoing posterior spinal fusion of at least 5 levels for correction of adult spinal deformity were randomized to 1 of 3 treatment groups. Primary outcome measures included intraoperative estimated blood loss, total loss, (estimated blood loss + postoperative blood loss), and transfusion rates. Results. Patients received TXA (n = 19), EACA (n = 19), or placebo (n = 13) in the operating room (mean ages: 60, 47, and 43 yr, respectively); TXA patients were significantly older and had larger estimated blood volumes than both other groups. Total losses were significantly reduced for EACA versus control, and there was a demonstrable but nonsignificant trend toward reduced intraoperative blood loss in both antifibrinolytic arms versus control. EACA had significant reductions in postoperative blood transfusions versus TXA. Conclusion. The findings in this study support the use of antifibrinolytics to reduce blood loss in posterior adult spinal deformity surgery. Level of Evidence: 1